DETERMINING TSUNAMI DISASTER PREPAREDNESS FOR STUDENTS IN BANTUL DISASTER PREPARED SCHOOL, YOGYAKARTA - Sri Yuni Tursilowati (JURNAL KESEHATAN INDRA HUSADA, 2020)
The Regional Disaster Management Agency (BPBD) mapped 52 villages in the southern region of Yogyakarta Special Region as an area prone to earthquakes and tsunamis. The potential of tsunamialong the southern coast of Java Island is due to the geographical location of Indonesia that is flanked by the Eurasia Asia - Australia plate and the Pacific and Philippine plates are quite active. Disaster preparedness school is the important key to protecting children and young people in creating a conducive and safe learning environment from unavoidable disasters. The purpose of this study was to determine the determinants of tsunami disaster preparedness in disaster preparedness school students in Kretek Bantul. This research method is descriptive quantitative using cross-sectional design. The population to be taken in this study were students of SMPN 2 Kretek Bantul Disaster Alert School Sampling using a purposive sampling technique with the number of samples in this study were 115 students. The results of this study indicate that the determinants of students' tsunami disaster preparedness at SMP Negeri 2 Kretek Bantul are knowledge, attitudes, awareness, and experience factors, while the factors that do not affect preparedness are perceptions and infrastructure.